2017
DOI: 10.1002/hep.29242
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abstinence ameliorates the dysregulated immune profiles in patients with alcoholic hepatitis: A prospective observational study

Abstract: Alcoholic hepatitis (AH) develops only in small proportion of heavy drinkers. To better understand the mechanisms underlying this disparity, we conducted a study to define the relationship between AH development and dysregulated immune responses that might be ameliorated by alcohol abstinence. Sixty-eight AH patients, 65 heavy drinking controls without liver disease (HDC), and 20 healthy controls (HC) were enrolled and followed up to 12 months. At the baseline, HDC and HC had no significant differences in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 46 publications
2
47
0
2
Order By: Relevance
“…Alcohol abstinence significantly improves disease outcome and survival but does not lead to complete recovery in most patients with AH . Consistent with this, we have recently reported that plasma levels of IL‐8 and TNF‐α are not normalized in abstinent patients with AH . Here, we identified four additional sICPs (sCD27, sCD40, sHVEM, and sTIM3) that were not fully reversed in abstinent patients with AH.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Alcohol abstinence significantly improves disease outcome and survival but does not lead to complete recovery in most patients with AH . Consistent with this, we have recently reported that plasma levels of IL‐8 and TNF‐α are not normalized in abstinent patients with AH . Here, we identified four additional sICPs (sCD27, sCD40, sHVEM, and sTIM3) that were not fully reversed in abstinent patients with AH.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we systematically profiled 18 sICPs in the plasma samples from a large cohort of patients with AH, HDCs, and HCs. In line with profound immune dysregulation in patients with AH, (3,19) we found that 17 out of 18 sICPs examined here were dysregulated (six up-regulated and 11 down-regulated). A previous study found that the TIM-3 ligand galectin-9 was elevated in patients with AH.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations